Impact of Reduced Activator Concentration and Curing Method on Compressive Strength of Metakaolin/Fly Ash-based Geopolymer Mortar - Harmaji, Andrie; Haimir, Alexander Syahlendra; Sunendar, Bambang (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2023)
The demand for cement is increasing each year, but the manufacture of 1 tonne of cement produces an equal number of carbondioxide (CO2) gas which is directly related to the increase in global warming. Therefore, we need a substitute material, namely geopolymer. This material has relatively superior properties compared to cement. However, one of the drawbacks of geopolymers is that the production costs are relatively more expensive compared to the manufacture of pre-cast cement because it requires chemical solutions such as sodium hydroxide (NaOH) and sodium silicate (Na2SiO3) to activate the precursor. This research was conducted to replace a specific ratio of alkali activator with water to reduce the use of alkaline hydroxide solutions and sodium silicate while reducing production costs. The experiment was carried out by replacing the activator solution with water at a certain amount with a different curing method. Mechanical properties, X-Ray Diffraction (XRD), and Fourier Transform Infrared (FTIR) spectroscopy characterization were used to analyze the effect of additional water in geopolymer. The compressive test result shows that the maximum water content that can replace the activator solution is 20% by activator mass for fly ash-based geopolymers and 30% by activator mass for metakaolin-based geopolymers, with sealed and bare curing conditions before the compressive strength was decreased sharply. Substitution of 10% water in fly ash-based geopolymer increases the compressive strength to 17.20 MPa. Compressive test results and characterization showed that the optimal curing condition for fly ash-based geopolymer was sealed curing and bare curing for metakaolin-based geopolymer. The strength increase is due to O-C-O bonds representing sodium carbonate (Na2CO3), which affects the compressive strength of fly ash-based and metakaolin-based geopolymers.